2023
DOI: 10.1093/ptj/pzad012
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Exercise Capacity and Activities of Daily Living in Individuals with Bronchiectasis Versus Healthy Controls

Abstract: Objective The purpose of this study was to compare the upper extremity exercise capacity and activities of daily living (ADLs) in individuals with bronchiectasis and controls. Methods Twenty-four individuals with bronchiectasis and 24 healthy controls were assessed for upper extremity exercise capacity (6-minute pegboard and ring test [6PBRT]) and ADLs (Glittre ADL test). Energy expenditure was measured using a wearable metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…This causes them to fail at upper extremity exercises at low workloads (Cakmak et al, 2023). In the present study, we observed that the median TGlittre time in CF patients was 3.17 min, well above that observed in CG patients.…”
Section: Discussionmentioning
confidence: 41%
See 4 more Smart Citations
“…This causes them to fail at upper extremity exercises at low workloads (Cakmak et al, 2023). In the present study, we observed that the median TGlittre time in CF patients was 3.17 min, well above that observed in CG patients.…”
Section: Discussionmentioning
confidence: 41%
“…Since the muscles that move the arm are attached to the rib cage, they stabilize the trunk but considerably increase the resistance of the chest wall in CF, limiting the ability to increase tidal volume during arm activities. This causes them to fail at upper extremity exercises at low workloads (Cakmak et al., 2023). In the present study, we observed that the median TGlittre time in CF patients was 3.17 min, well above that observed in CG patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations